Penerapan Model Pembelajaran Cooperative Script Pada Siswa Kelas VII SMP Negeri 12 Kota Ternate Untuk Meningkatkan Hasil Belajar IPA - Endang Fitria (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is a classroom action research that aims to find out whether the Cooperative Script learning model can improve science learning outcomes for class VII students of SMP Negeri 12 Kota Ternate. The research method used was qualitative and the subjects of this study were class VII students of SMP Negeri 12 Kota Ternate with a total of 29 students. Sources of data from teachers and students. Research data collection techniques were carried out using observation sheets carried out by learning models and test questions. The data obtained were analyzed by descriptive qualitative. The results showed that the average score of students in cycle I was 68. Meanwhile, in cycle II, the average score of students was 79.83. This shows an increase in science learning outcomes. From the results of this study it can be concluded that applying the cooperative script learning model to class VII students of SMP Negeri 12 Kota Ternate can increase.